Pengaruh Keberadaan Sistem Budidaya Ikan dalam Jaring Apung terhadap Tingkat Trofik Perairan Waduk Mrica Banjarnegara - Agatha Sih Piranti; Christiani . (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
Organic waste from aquaculture discharged into the aquatic ecosystem can cause negative impact of this water. The occurrence of one or more plankton blooming has a toxic to other aquatic organisms including fish cultured. The purpose of this research was to know the influence of floating nets fish farming to the trophic level of the Mrica Reservoir based on the diversity of plankton. This research used a survey method in three stations (1) inlet area (2) inside/near the location of the floating net (3) outlet area. The sampling was conducted 4 times during a month (August) with interval of a week. The major parameters were the concentration of nutrients (N dan P) and the abundance of plankton. The supporting parameters were the BOD, DO and carbon dioxide concentration, pH, temperature and light penetration. The t analysis was used to compare whether there was any difference of nutrients load among the stations. The diversity index was calculated to evaluate the quality of the ecosystem based on The Water Quality Standard followed by calculation of Saprobic Coefficient to know the trophic level of the ecosystem. The results of this research showed that the occurrence of floating nets fish farming resulted in the increased of nutrients load, and consequently the trophic level of this ecosystem is in b-meso/oligosaphrobik (light pollution). Ceratium sp dominated the Mrica Reservoir.